Positronium scattering from ions, atoms and molecules - Biswas, P. K. (Elsevier B.V., 2000)
Elastic and inelastic scattering of positronium (Ps) by H, He, He(+) and H(2) have been studied using coupled-channel calculations with a regularised nonlocal model exchange potential. Suitability and reliability of the theoretical scheme have been demonstrated by studying scattering cross-sections in various systems and also by addressing critical dynamic features like binding and resonances of Ps to open-shell-atoms. Results are found to be in good agreement with Variational predictions and experimental observations. (C) 2000 Elsevier B.V. Ltd. All rights reserved.